Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1902/jop.1990.61.8.521
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Indicators for Periodontal Attachment Loss in a Population of Older Community‐Dwelling Blacks and Whites

Abstract: The extent and severity of periodontal attachment loss are described for a random sample of 690 dentate community-dwelling adults, aged 65 or over, residing in five counties in North Carolina. In addition, risk indicators for serious levels of loss of attachment and pocket depth in this population are presented. Pocket depths and recession were measured on all teeth by trained examines during household visits. Blacks had an average of 78% of their sites with attachment loss and the average level of loss in tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
221
0
10

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(252 citation statements)
references
References 5 publications
21
221
0
10
Order By: Relevance
“…Periodontitis progresses discontinuously throughout life and the prevalence in cross-sectional studies in advanced age has more to do with a lifetime of AL than any increased incidence in the elderly. 5,15,16 Nonetheless, in cross section, it is clear that older age groups (65+ years) have increased AL, multivariate studies having demonstrated ORs for AL as high as 9.01 (95% CI: 5.86 13.89), constituting the most signifi cant risk indicator in periodontal disease. 17 It is recognised as a product of disease expe rience throughout life rather than some thing intrinsic with being older.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Periodontitis progresses discontinuously throughout life and the prevalence in cross-sectional studies in advanced age has more to do with a lifetime of AL than any increased incidence in the elderly. 5,15,16 Nonetheless, in cross section, it is clear that older age groups (65+ years) have increased AL, multivariate studies having demonstrated ORs for AL as high as 9.01 (95% CI: 5.86 13.89), constituting the most signifi cant risk indicator in periodontal disease. 17 It is recognised as a product of disease expe rience throughout life rather than some thing intrinsic with being older.…”
Section: Agementioning
confidence: 99%
“…8,17 All factors show a positive cor relation, with periodontal disease preva lence attributed to a 'differential access to resources and opportunities that may influence preventive behaviours', with OR as high as 3.10 (95% CI: 1.64-6.03), indi cating a statistically signifi cant divide between those that have attended some 3rd level education and those who have not. 15,21 Other multivariate clinical anal yses have put the OR even higher, though it is perhaps difficult to completely sepa rate SES from other, more physiological variables. 22 Socioeconomic status may represent a measure of personal drive and motivation, and may impact on the quality of oral hygiene habits, and as such represents a valid risk indicator.…”
Section: Socioeconomic Status (Ses)/educationmentioning
confidence: 99%
“…[77][78][79][80][81] In Bangladesh, a large number of the people still live in low socioeconomic condition; the country's gross national income per capita was only USD 2,030,3.6% of GDP was for total health expenditure, and the per capita health expenditure was only USD 68 in 2012. 82 This low-income population in general is more prone to malnutrition and infection, and becomes victim to poor oral hygiene, including PD.…”
Section: Low Socioeconomic Conditionmentioning
confidence: 99%
“…that they are of multifactorial etiology (Kleinbaum et al 1982). In a relatively large number of cross-sectional studies, multiple risk putative risk factors for periodontal disease have been examined (Beck et al 1990, Grossi et al 1994, Horning et al 1992, Ismali & Szpunar 1990). …”
Section: Risk Factors For Periodontitismentioning
confidence: 99%